Stability Analysis of Steel Welded Tubes Forming Process Using Numerical Simulations - Delić, Marko; Mandić, Vesna; Popović, Marko (2021)
In this paper, the research results of the stability of steel welded tubes forming process are presented. The aim of this research is to determine influence of geometrical and tribological parameters on stability of the process and to determine optimal values of influential process parameters. A research plan with variation of influential parameters was made, on the basis of which experimental and numerical experiments were performed. Tube forming was performed in one operation in a two-part tool made of hard metal by a combination of widening and narrowing. The geometrical factors observed during experiments are length, outer diameter and thicknesses of steel welded tube as a billet. Friction conditions in contact between tool and tubular workpiece are considered in two cases, the first one when standard machine oil is used as a lubricant and the second one when tube billet surface is phosphated. Based on results of experiments, influencing factors on stability of tube forming process were analysed and optimal production technology was recommended, including optimal values of influencing factors. Results obtained by experimental research were confirmed through numerical experiments based on finite element method.
Bibliografija
Summary.